NILAI-NILAI PENDIDIKAN DALAM ALQURAN SURAH AL-LAHAB (STUDI ANALISIS TAFSIR AL-QURAN) - Lukman Hakim Ritonga, Achyar Zein, Zulheddi (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2018)
Abstrak: The purpose of this study is to describe what the values of education in the Koran are for Q.S.al-Lahab and the application of educational values to the surah al-Lahab in the world of education. Theresearch methodology carried out by the author here is by using the library (library research) The results ofthis study indicate some of the educational values contained in the surah al-Lahab globally, namelyaqidah and akhlak education. Among the values of education that are understood, namely the educationalvalue of faith/creed which is the form of disbelief and belie the truth, and reject the religion broughtby the Prophet Muhammad will be able to bring a person into hell, instead someone who obeys andbelieves in the end and day of vengeance will become a group of believers and enter into heaven. The valueof moral education that can be concluded is: the obligation to protect themselves from despicable qualitiesincluding the nature of evil, jealousy, the nature of spreading slander which is not true, and envy of humans.And is obliged to take care of yourself from the fire of hell such as happy to spread bad traits,eventually going back to yourself, then still keeping the family from the characteristics that bring about thewrath of Allah Almighty. Implicitly the surah al-Lahab contained educational values which were concludedamong others; 1) the value of moral and attitude coaching, 2) the concept of achieving wealth andlearning towards the blessing of Allah swt, 3) avoiding the nature of slander.Adapun tujuan penelitian ini adalah untuk mendeskripsikan apa saja nilai-nilai pendidikan dalam Alquranpada Q.S. al-Lahab dan aplikasi nilai-nilai pendidikan pada surah al-Lahab dalam dunia pendidikan.Metodologi penelitian yang dilakukan penulis disini dengan menggunakan kepustakaan (library research).Hasilpenelitian ini menunjukkan beberapa nilai pendidikan yang terdapat dalam surah al-Lahab secara globalyaitu pendidikan akidah dan akhlak. Di antara nilai pendidikan yang dipahami, yaitu nilai pendidikankeimanan/akidah yaitu bentuk kekafiran dan mendustakan kebenaran, dan menolak agama yang dibawaNabi Muhammad saw akan dapat membawa seseorang terseret masuk ke dalam neraka. Nilai pendidikanakhlak yang dapat disimpulkan yaitu: kewajiban untuk menjaga diri dari sifat-sifat tercela di antaranyasifat ba!il, sifat iri dengki, sifat menyebar fitnah yang tidak benar kebenarannya dan iri hati terhadapmanusia. Dan diwajibkan untuk menjaga diri sendiri dari api neraka seperti senang menyebar sifat buruk,pada akhirnya akan kembali kepada diri sendiri, kemudian tetap menjaga keluarga dari sifat-sifat yangmendatangkan kemurkaan Allah swt. Secara implisit surah al-Lahab terdapat nilai-nilai pendidikan yangdisimpulkan antara lain; 1) nilai pembinaan moral dan sikap, 2) konsep meraih harta dan menuntut ilmumenuju ridha allah swt, 3) menjauhi dari sifat fitnah.Kata Kunci: Nilai, Pendidikan Islam, Surah al-Lahab, Alquran